2017
DOI: 10.18632/oncotarget.20829
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability and acquired drug resistance in multiple myeloma

Abstract: Chromosomal instability (CIN) is an important hallmark of human cancer. CIN not only contributes to all stages of tumor development (initiation, promotion and progression) but also drives, in large measure, the acquisition of drug resistance by cancer cells. Although CIN is a cornerstone of the complex mutational architecture that underlies neoplastic cell development and tumor heterogeneity and has been tightly associated with treatment responses and survival of cancer patients, it may be one of the least und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…107) might provide novel drug targets that could overcome the drug resistance associated with CIN, especially when combined with therapies that target known tumor suppression or oncogenic pathways or signal transduction in cancer patients. Some studies indicate that CIN modulates tumor heterogeneity in patients with myeloma and contributes to acquired drug resistance in multiple myeloma (108). As a result, targeting CIN upfront can be a potential approach to prevent genetic heterogeneity from occurring; new experimental model systems of CIN-dependent malignancy are needed for developing new therapies (108).…”
Section: Combination With Chemotherapy To Overcome Resistancementioning
confidence: 99%
“…107) might provide novel drug targets that could overcome the drug resistance associated with CIN, especially when combined with therapies that target known tumor suppression or oncogenic pathways or signal transduction in cancer patients. Some studies indicate that CIN modulates tumor heterogeneity in patients with myeloma and contributes to acquired drug resistance in multiple myeloma (108). As a result, targeting CIN upfront can be a potential approach to prevent genetic heterogeneity from occurring; new experimental model systems of CIN-dependent malignancy are needed for developing new therapies (108).…”
Section: Combination With Chemotherapy To Overcome Resistancementioning
confidence: 99%
“…Decades of fundamental and clinical research have shown that CIN has tremendous implications in cancer development, progression, and clinical outcomes ( Figure 1). For example, CIN is associated with cellular transformation [9,50], tumor evolution and progression including intertumoral and intratumoral heterogeneity [51][52][53], metastasis [54][55][56], and the acquisition of drug resistance [57,58]. Thus, it is perhaps unsurprising that the presence of CIN is typically associated with worse patient outcomes [59][60][61][62].…”
Section: The Impact Of Cin On Cancer Development and Progressionmentioning
confidence: 99%
“…This is especially relevant, as a protracted disease course inevitably leads to extensive genetic diversity within a CIN tumor cell population, such that the cells present in a late stage tumor are genetically disparate from those biopsied or removed at the time of primary surgery in early stage disease [155]. Furthermore, as CIN confers multidrug resistance [57,58], single agent strategies typically fail due to the ineffectiveness of the treatment across the entire tumor population and/or the adaptive nature of the cells exhibiting CIN. Thus, the accuracy of prognostic stratification will likely provide limited insight, as the diagnostic information is restricted to the region that is analyzed.…”
Section: The Impact Of Cin On Therapeutic Targetingmentioning
confidence: 99%
“…Advances in surgical techniques, cancer-specific therapies and small molecule inhibitors have contributed to survival and disease-free duration [1]. However, the development of multiple drug resistance (MDR) to first-line chemotherapeutic agents leaves few, if any, proven treatment options, and may signal a shift to palliative support rather than active therapy [2][3][4][5][6]. MDR can be inherent (prior to treatment) or acquired at any time after initial treatment responsiveness, with recrudescence as much as 20 years later [7,8].…”
Section: Introductionmentioning
confidence: 99%